DETERMINANTS OF FINANCIAL PERFORMANCE IN MANUFACTURING FIRMS: THE ROLE OF CAPITAL STRUCTURE, LIQUIDITY, AND FIRM SIZE - Mangasi Sinurat; Nursaimatussaddiya; Rico Nur Ilham; Frengki Putra Ramansyah (Universitas Efarina, 2026)
Purpose – This study examines the effect of capital structure, liquidity, and firm size on financial performance. This topic is important because financial performance reflects a company’s ability to generate profits and sustain its operations, while internal financial factors such as debt policy, liquidity position, and firm scale play a crucial role in determining that performance. Design/methodology/approach – This research employs a quantitative approach using secondary data derived from companies’ financial statements. The analysis is conducted using multiple regression, with hypothesis testing through t-tests to assess partial effects and F-tests to evaluate simultaneous effects of the independent variables on financial performance. Findings/Results – The results show that capital structure has a negative and significant effect on financial performance, while liquidity and firm size have positive and significant effects. These findings indicate that lower reliance on debt and stronger liquidity positions contribute to improved profitability, and larger firms tend to perform better financially. Originality/Value – This study highlights the importance of balancing debt usage, maintaining liquidity, and leveraging firm size to enhance financial performance. The findings provide practical implications for managers in making financial decisions and contribute to the existing literature by offering empirical evidence on the combined effects of these key financial factors.